2014
DOI: 10.1248/bpb.b14-00417
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Terfenadine and Pentamidine on the hERG Channel and Its Intracellular Trafficking: Combined Analysis with Automated Voltage Clamp and Confocal Microscopy

Abstract: The effects of terfenadine and pentamidine on the human ether-a-go-go related gene (hERG) channel current and its intracellular trafficking were evaluated. Green fluorescent protein (GFP)-linked hERG channels were expressed in HEK293 cells, and the membrane current was measured by an automated whole cell voltage clamp system. To evaluate drug effects on channel trafficking to the cell membrane, the fraction of channel present on the cell membrane was quantified by current measurement after drug washout and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…It appears that KCNH K + channels should be localized to plasma membrane. However, as previously reported, the staining of KCNH-class channels was not restricted to plasma membrane but rather was diffused throughout cytosol Tanaka et al, 2014;Uhlé n et al, 2015). KCNH6 is also expressed in a cells, and it is surprising that glucagon secretion is unaltered in this study.…”
Section: Discussionsupporting
confidence: 75%
“…It appears that KCNH K + channels should be localized to plasma membrane. However, as previously reported, the staining of KCNH-class channels was not restricted to plasma membrane but rather was diffused throughout cytosol Tanaka et al, 2014;Uhlé n et al, 2015). KCNH6 is also expressed in a cells, and it is surprising that glucagon secretion is unaltered in this study.…”
Section: Discussionsupporting
confidence: 75%
“…In addition to this, we found several other classes of drugs showing activity against hERG in the present assay, such as antihistamine drugs (Astemizole, Terfenadine, Clemastine, Ebastine), prokinetic drugs (Cisapride, Domperidone), and some chemotherapeutic agents (Lapatinib, Bosutinib methanoate). The ability of these non-CV drugs to induce QT interval prolongations or arrhythmias has been established by various studies [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. One of the most well-known chemotherapeutic agents with cardiotoxic effects is 5-fluorouracil, which was tested here, but was inactive, consistent with the hypothesized mechanisms of direct cellular damage and/or ischemia, rather than hERG channel inhibition [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments on compound–protein interactions are required to qualify these drugs as Hsp90-targeted inhibitors. Although a variety of drugs have been shown to interfere with hERG transport to reduce current, direct blockade of drugs without trafficking defects has also been reported ( Borsini et al, 2012 ; Tanaka et al, 2014 ). Recently, a study of the effects of COVID-19 drugs chloroquine and hydroxychloroquine on blocking the hERG potassium channel showed that these drugs acutely and severely inhibited the hERG current, but remdesivir increased the I hERG with promoted hERG maturation when acting alone ( Szendrey et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%